2015
DOI: 10.1016/j.jpainsymman.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Limits and Responsibilities of Physicians Addressing Spiritual Suffering in Terminally Ill Patients

Abstract: Most physicians believe that spiritual suffering tends to intensify physical pain and that physicians should seek to relieve such suffering. Physicians who believe they should address spiritual suffering just as much as physical pain report more success in relieving patient's suffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Moreover, it has been shown that religious beliefs impact the concrete practice of various fields of medicine such as general practice [43], psychiatry [44, 45], gynaecology [46], and end-of-life-care [47]. This research documents how such beliefs may have significant impact on the practice of medicine, including ODT.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, it has been shown that religious beliefs impact the concrete practice of various fields of medicine such as general practice [43], psychiatry [44, 45], gynaecology [46], and end-of-life-care [47]. This research documents how such beliefs may have significant impact on the practice of medicine, including ODT.…”
Section: Discussionmentioning
confidence: 82%
“…Positive attitudes towards PS-ES varied widely, with the following percentage of the physicians showing positive attitudes: 6.8%,29 22%,30 31%,25 26 42.1%,31 37%–61%28 and 68% positive attitudes 27. The range of negative attitudes varied widely also, with the following percentage of physicians showing negative attitudes: 14.3%,29 17.1%,31 34%,25 26 23%–43%28 and 64% negative attitudes 30. The percentages of participants having neutral or undecided attitudes were 14%,30 16%–20%,28 29.6%31 and 47% 29.…”
Section: Resultsmentioning
confidence: 98%
“…A total of 1955 papers was screened (figure 1), but only 17 met our inclusion criteria. Seven studies were reports of quantitative studies,25–31 seven were reports of qualitative studies32–38 and three39–41 were reports of mixed-methods studies. The included articles were published between 2002 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations